Energy Efficiency and Greenhouse Gas Emissions Reduction Through Electrification Program atTanjungEnim Mine Business Unit of PT Bukit Asam (Persero) Tbk. - Iko Gusman; Pramudita Triatmojo; Peni Rostiarti; Bima Arifiyanto (Research Centre of Inorganic Materials and Complexs, 2018)
Current global economic conditions have made the coal prices become uncertain. PT Bukit Asam (PTBA) has taken corporate action by improving operational efficiency, cost control, develop coal diversification product and also optimizationin the mining operation. One of the operational efficiency programs for cost control in mining operation system is the Electrification Program. This program changed mining operations previously dominated by fuel-based mining system transformed into an electricity-based mining system for an electricshovel continue with the conventional truck. Implementation of Mining Systems with electric-based mining equipment divided into several stages for short-term and long-term targets. Electrification program consist of 7 Units Electric Shovel (PC3000-6E) and 40 Units Rigid DT (Belaz75135) with target20 Million BCM in 2017 located inBanko West Mine. PTBA through the electrification program has succeeded in reducing energy consumption by 333,861.74 GJoule/Years and reducing greenhouse gas emissions by 15,058.49 Ton CO2e/Year. Electrification program has successfully contributed for environmental sustainability by reducing energy consumption and greenhouse gas emissions in accordance with the vision of PTBA into a world-class energy company that cares about the environment.